Metachronous isolated locally advanced pancreatic metastasis from chromophobe renal cell carcinoma. (2019) - Ayari, Y.; Ben Rhouma, S.; Boussaffa, H.; Chelly, B.; Hamza, K.; Sellami, A.; Jrad, M.; Nouira, Y.
Highlights: Isolated pancreatic metastasis from renal cell carcinoma is relatively rare and it's usually seen in clear cell renal cell carcinoma (CCRCC), but its occurrence from chromophobe renal cell carcinoma is extremely rare. Pancreatic location is often diagnosed during routine surveillance imaging for the primary lesion. Patients in whom the pancreas is the only metastatic site and who are fit enough to undergo pancreatic surgery appear to be good candidates for the surgical treatment chemotherapy can improve the quality of life but not survival. It is necessary a long- term follow-up for patients treated for tumors with known low-grade metastatic potential and relatively good prognosis such as chromophobe renal cell carcinoma. Abstract: Introduction: Metastasis to the pancreas is relatively uncommon occurrence. Isolated pancreatic metastasis from renal cell carcinoma (RCC) is relatively rare and it's usually seen in clear cell renal cell carcinoma (CCRCC), but its occurrence from chromophobe renal cell carcinoma (chRCC) is extremely rare, due to its relatively low-grade metastatic potential. Presentation of case: The authors report an unusual case of metachronous isolated pancreatic metastasis, in a 65-year-old female patient two years after left nephrectomy for chRCC, diagnosed during routine surveillance imaging and confirmed after a CT-guided pancreatic biopsy. Discussion: The pancreas is an elective site for metastases from RCC, and this particularity has been reported by several studies, but only described for CCRCC. In the English literature there is only one case of pancreatic metastasis from chRCC diagnosed in an autopsy study. Surgical resection of metastasis remains the most effective treatment, particularly for pancreatic metastases from chRCC, since radiotherapy, chemotherapy, hormonal therapy, and targeted therapy have generally proved ineffective for metastatic chRCC. In case of an unresectable disease, surgical or endoscopic palliation in association with palliative chemotherapy can improve the quality of life but not survival. Conclusion: This case highlights the unique behavior of chRCC with an unusual site of metastasis, and the necessity of long-term follow-up after primary tumor removal, even if it is known for a low-grade metastatic potential and a relatively good prognosis.